Preparation and Characterization of Electrodes Modified with Pyrrole Surfactant, Multiwalled Carbon Nanotubes and Metallophthalocyanines for the Electrochemical Detection of Thiols - Zagal-Moya, J; Zagal-Moya, J (2014)
Our aim was to prepare hybrid electrodes active towards the electrooxidation of thiols by the co-immobilization of native carbon nanotubes (CNTs) and cobalt phthalocyanine (CoPc) from aqueous solutions. This strategy was adopted to avoid the oxidation of CNTs that can induce a modification of their exceptional properties. To do so, a hydrosoluble pyrrole surfactant was used to get homogeneous aqueous dispersions of CNTs and CoPc and to trap both materials on the electrode via the electropolymerization of the pyrrole surfactant. The hybrid electrodes exhibit a good electrocatalytic activity towards the oxidation of L-cysteine and glutathione. Their performances in terms of limit of detection (0.01mM) are compatible with the detection of these thiols in biological samples. © 2014 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.